Staged total percutaneous treatment of aortic valve pathology and mitral regurgitation: Institutional experience. Issue 4 (25th May 2013) - Kische, Stephan; D'Ancona, Giuseppe; Paranskaya, Liliya; Schubert, Jochen; Arsoy, Nicole; Hauenstein, Karl Heinz; Alozie, Anthony; Jovanovich, Bojan; Nienaber, Christoph; Ince, Hüseyin
<x xml:space="preserve">Abstract</x> Objectives To summarize our single Institution experience with staged total percutaneous management of aorto‐mitral pathology. Background Percutaneous treatment of aortic valve stenosis (AVS) and mitral valve regurgitation (MVR) has been recently proposed for patients at high surgical risk. Methods Data concerning consecutive patients undergoing percutaneous transcatheter AV implantation (TAVI) followed by MV repair with MitraClip® were prospectively collected and analyzed. Results From January 2010 to February 2012 a total of 254 patients were referred to undergo TAVI in our Institution. Seventeen (6.7%) had preoperative severe MVR that remained unchanged after TAVI. Due to exacerbation of symptoms 12 patients were subsequently submitted to MV repair with the MitraClip® device. Mean age was 79 years (72–86 years), median Ambler score was 30.1 (17.2–42.6) and EuroSCORE 22.3 (10.2–48.6). Procedural success rate was 100%. Postprocedural hospitalization was 7.1 ± 2.7 and 4.6 ± 0.9 days after TAVI and MV repair, respectively. Six months follow‐up echocardiography confirms improvement in LV‐EF (37.2 ± 9.9 vs. 43.5 ± 10.7, P < 0.0001). No patient presents MVR exceeding grade I+ or prosthetic aortic insufficiency > I grade and all patients experienced an improvement in functional status. Conclusions Percutaneous treatment of AVS and MVR is feasible and safe. A tailored approach should be considered to treat firstly the AVS and subsequently the MVR when severe MV dysfunction and symptoms persist. Short‐term durability of this combined percutaneous approach seems encouraging and justifies the economical burden to treat patients that have no other option. © 2013 Wiley Periodicals, Inc.